Evidence of segmentation and persistent labor exclusion in Argentina - Sconfienza, María Eugenia (2016)
The population of workers in Argentina is comprised of advantaged and disadvantaged sectors. In a period in which an important part of labor indicators have improved, persistent segmentation merits reflection. Recent years show evidence of persisting precariousness and fragmentation of the poorer working class. Based on the data from the Permanent Household Survey (EPH) periodically prepared by the National Statistics and Census Bureau in Argentina (INDEC), this paper describes some labor market indicators observed between 2004 and 2012 which evidenced this dynamic. It was in this period when a set of socio-economic protection measures were applied, which led to some recovery after the crisis at the beginning of the century. It is observed that workers with the most precarious conditions are those with lower levels of education (particularly women), work in smaller businesses, and are less qualified (those not qualified doubled the level of informality with respect to professionals).